Brand Personality of Business Schools in Chile: Model Proposal - Araya-Castillo, L; Escobar-Farfan, M (UNIV EAFIT, 2015)
This research presents the model "Business School Brand Personality" (BSBP), which fulfils all the requirements of content validity. The BSBP model is based on the brand personality model of Aaker (1997), but it adapts to the unique characteristics of business schools in Chile. In order to detect the dimensions of the BSBP model, an exhaustive literature review was performed, semi-structured questionnaires, as well as interviews and focus groups for students were applied, and expert opinions were seeked. The participation of undergraduate and postgraduate students was taken into account, therefore the proposed model applies to business schools as a whole, and not to a particular type of students. As a result, the BSBP was proved to be multidimensional and composed of the following dimensions: a) competition, b) innovation, c) sincerity, d) enthusiasm, e) rudeness, f) elitist, g) ambition, and h) social. The results contribute to the literature, because it is the first model proposed for business schools. Consequently, the proposed model can be used as a first approximation for research taking place focusing on higher education sectors in other countries.
Keywords: Brand Personality; Business Schools; Theoretical Model; Personality Traits; Chile